A Current Overview of Cyclodextrin-Based Nanocarriers for Enhanced Antifungal Delivery - Hay Man Saung Hnin Soe; Phyo Darli Maw; Thorsteinn Loftsson; Phatsawee Jansook (MDPI AG, 2022)
Fungal infections are an extremely serious health problem, particularly in patients with compromised immune systems. Most antifungal agents have low aqueous solubility, which may hamper their bioavailability. Their complexation with cyclodextrins (CDs) could increase the solubility of antifungals, facilitating their antifungal efficacy. Nanoparticulate systems are promising carriers for antifungal delivery due to their ability to overcome the drawbacks of conventional dosage forms. CD-based nanocarriers could form beneficial combinations of CDs and nanoparticulate platforms. These systems have synergistic or additive effects regarding improved drug loading, enhanced chemical stability, and enhanced drug permeation through membranes, thereby increasing the bioavailability of drugs. Here, an application of CD in antifungal drug formulations is reviewed. CD-based nanocarriers, such as nanoparticles, liposomes, nanoemulsions, nanofibers, and in situ gels, enhancing antifungal activity in a controlled-release manner and possessing good toxicological profiles, are described. Additionally, the examples of current, updated CD-based nanocarriers loaded with antifungal drugs for delivery by various routes of administration are discussed and summarized.